Keseimbangan Kerja-Kehidupan Berpengaruh Pada Kesejahteraan Psikologis Pekerja - Dewi Savitri, Maya (CV. Multi Kreasi Media, 2024)
Psychological well-being is an individual's psychological ability which he or she successfully accepts his strengths and weaknesses, has a purpose in life, able to develop positive relationships with others, has an independent personality, able to controls the environment, and conducts personal development. Work-life balance is an individual's ability to balance his personal and work life. This study aims to obtain empirical evidence regarding the effect of work-life balance on the psychological well-being of workers in several regions in Indonesia. The research method used quantitative study, and data collected through questionnaires. Respondents was 102 workers, who has various demographic and occupations backgrounds. The results showed that there was a significant influence (9.2%) of work-life balance on workers’ psychological well-being. There were no differences in psychological well-being and work-life balance related to demographic aspects (gender, age, marital status, and education level) and occupational aspects (employment status and employment period).